Differences in Ibn Ma'in's Judgments on Narrators Through the Transmission of His Statements in His Book "Al-Tarikh" – A Critical Applied Study - Adib Muhammad Hasan,; Adib Muhammad Hasan, (Islamic Sciences Journal, 2025)
ABSTRACT This research examines the status of the narrators whose reliability or weakness was assessed differently by Ibn Ma'in, as transmitted by his students. It compares these judgments with those of other scholars of Hadith criticism to determine the extent to which his evaluations align with the experts in the field. The study consists of an introduction, two main sections, and a conclusion. The first section provides a biography of Ibn Ma'in and identifies the reliable transmissions of his work "Al-Tarikh." The second section presents some applied examples that form the basis of the critical study's methodology. The conclusion highlights some of the key findings derived from the research.